2021
DOI: 10.1007/s10067-021-05730-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mitochondrial autoantibodies are associated with cardiomyopathy, dysphagia, and features of more severe disease in adult-onset myositis

Abstract: We analyzed the prevalence of anti-mitochondrial autoantibodies (AMA) in adult- and juvenile-onset myositis longitudinal cohorts and investigated phenotypic differences in myositis patients with AMA. We screened sera from myositis patients including 619 adult- and 371 juvenile-onset dermatomyositis (DM, JDM), polymyositis (PM, JPM), inclusion body myositis (IBM), or amyopathic DM patients and from healthy controls, including 164 adults and 92 children, for AMA by ELISA. Clinical characteristics were compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 15 publications
3
25
2
Order By: Relevance
“…The authors found that 1% (4 of 371) of children with JDM and healthy controls (1 of 92) had AMA detected by ELISA. All 4 JDM patients with AMA had severe disease at onset with falling episodes and 3 out of the 4 had dysphagia (85). Though the detection of AMA was shown to be very rare in JDM patient sera this study suggested that it may predict worse disease for these patients.…”
Section: Pathogenic Mechanism and Biomarkersmentioning
confidence: 67%
“…The authors found that 1% (4 of 371) of children with JDM and healthy controls (1 of 92) had AMA detected by ELISA. All 4 JDM patients with AMA had severe disease at onset with falling episodes and 3 out of the 4 had dysphagia (85). Though the detection of AMA was shown to be very rare in JDM patient sera this study suggested that it may predict worse disease for these patients.…”
Section: Pathogenic Mechanism and Biomarkersmentioning
confidence: 67%
“…AMA positivity was not recorded in any of the children included in the cohort. A recent study showed that 1% of the juvenile myositis cases (3 of 302 jDM, 1 of 25 jPM) tested positive for AMA although they did not have any cardiac involvement 24 . Literature is sparse on this subject and requires further study from pediatric centers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, dysphagia was noticed as significantly more frequent both in AMA-positive adults and children. 124 The authors stated, as a conclusion, that detection of AMA should instigate physicians to monitor for cardiac and gastroesophageal dysfunction.…”
Section: Autoantibodiesmentioning
confidence: 99%